Peran Keagenan Kapal dalam Pembuatan Line-Up PT. Maritime Network Indonesia Cabang Dumai Melalui Plotting Kapal di Pelabuhan Pelindo Dumai - Yogi Syahputra; Syarifur Ridho; Irma Handayani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to analyze the crucial role of the shipping agency—specifically PT. Maritime Network Indonesia Dumai Branch—in preparing the vessel departure and arrival schedule (line-up). Line-up preparation is a strategic process that involves vessel plotting at Pelindo Dumai Port and is vital for supporting the smooth running of port operations and loading/unloading activities. The research methodology includes field research (field research) to observe direct practices at the port and literature review (library research) to reinforce the theoretical and regulatory foundations. The findings confirm that the shipping agency plays an important role in ensuring the efficiency of the port schedule. Nevertheless, in practice, the line-up preparation process faces several significant challenges. These obstacles include the limited authority of local agents in independently determining vessel plotting, restricted coordination meeting schedules, and the continued use of manual and inefficient communication methods. This lack of integrated communication often leads to inaccuracies in the initial line-up preparation, forcing agents to recalculate the previously arranged vessel positions. The conclusion of this study suggests the need for developing an integrated system that facilitates real-time communication and reporting to all relevant agencies. Adopting a digital system will enhance process efficiency, ensure proper documentation, and minimize errors, thereby accelerating the vessel plotting coordination process in the field.